Pengaruh Leverage, Profitability, Growth Opportunity dan Liquidity Terhadap Cash Holding - Jesslyn Maxentia; Malem Ukur Tarigan; Verawati (Jurnal Ekonomi, 2022)
The purpose of this study was to obtain empirical evidence of the influence of leverage, profitability, growth opportunity, and liquidity on cash holding. The subjects in this study were manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2017 – 2019. The population in this study amounted to 56 companies. After being selected using the purposive sampling method, the research sample consisted of 17 companies and for three periods the number of data was 51. Eviews version 12.0 program was used for data processing. The result of this study indicates that growth opportunity has a significant positive effect on cash holding, while leverage, profitability, and liquidity have no significant effect on cash holding.